2022
DOI: 10.1093/rb/rbac035
|View full text |Cite
|
Sign up to set email alerts
|

The polycaprolactone/silk fibroin/carbonate hydroxyapatite electrospun scaffold promotes bone reconstruction by regulating the polarization of macrophages

Abstract: Macrophages are known to modulate the osteogenic environment of bone regeneration elicited by biological bone grafts. Alteration in certain chemical components tends to affect macrophages polarization. Comparatively to hydroxyapatite (HAp), carbonate hydroxyapatite (CHA) consists of 7.4 (wt%) carbonate ions and more closely resembles the mineral content of bone. It remains unknown whether CHA scaffolds or HA scaffolds have better osteogenic properties. In this study, we fabricated PCL/SF scaffold, PCL/SF/HAp s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The SF/calcium phosphate material has good biocompatibility and mechanical properties as a bone repair scaffold, providing a good growth space for osteoblast differentiation. In addition, the injectability exhibited by the hydrogel and its use as a drug carrier allows the hydrogel to fit closely to the interface of the cartilage defect, thus improving the integration effect [ 139 ].…”
Section: The Role Of Sf In Bone/cartilage Damagementioning
confidence: 99%
“…The SF/calcium phosphate material has good biocompatibility and mechanical properties as a bone repair scaffold, providing a good growth space for osteoblast differentiation. In addition, the injectability exhibited by the hydrogel and its use as a drug carrier allows the hydrogel to fit closely to the interface of the cartilage defect, thus improving the integration effect [ 139 ].…”
Section: The Role Of Sf In Bone/cartilage Damagementioning
confidence: 99%
“…In addition, recent studies have confirmed that some inorganic metal ions or drug molecules combined with CPC can promote the repair of osteoporotic fractures or bone defects [ 20 , 21 ]. Silk fibroin (SF) is a kind of natural high molecular protein secreted by silkworm and has a wide array of medical applications owing to its good biocompatibility, degradability, modification and stable mechanical properties [ 22 , 23 ]. It has been reported that SF combined with CPC can be used for implant fixation and bone tissue defects [ 24 ], and both CPC and SF have good loading properties for various drugs and biological factors [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%